Novel Three-Dimensional Morphometry to Reassess Orbit Deformities Associated With Orbital-Periorbital Plexiform Neurofibroma. Issue 2 (March 2019) - Guo, Chengrui; Chen, Liangbo; Qu, Yang; Hu, Xiaojie
Abstract : Background: Orbit deformities are usually found in neurofibromatosis type 1 patients, especially those with orbital-periorbital plexiform neurofibroma (OPPN). Unfortunately, current morphometry is complicated and, in some cases, cannot be performed on the deformed orbit due to the destruction of landmarks. Herein, we present a novel 3-dimensional (3D) morphometry for these orbital measurements. Methods: We retrospectively reviewed 29 patients with OPPN, and another 29 disseminated cutaneous neurofibroma patients served as controls. All patients had undergone craniofacial computed tomography and 3D reconstruction. New morphometry was used to measure the area of the orbital rim (OR) and superior orbital fissure (SOF). Results: For the 29 patients with OPPN, the area of the OR at the affected side was 14.18 ± 3.50 cm 2, while the OR at the nonaffected side was 12.32 ± 1.38 cm 2 . In addition, the area of the SOF at the affected side was 5.37 ± 5.75 cm 2, while that at the nonaffected side was 1.27 ± 1.03 cm 2 . The OR and SOF at the affected side are more likely to become enlarged compared with those at the nonaffected side. Among the 29 patients with OPPN, the novel morphometry could be performed in 19 cases (65.5%) that cannot be measured by previous morphometry. Conclusion: The novel morphometry is convenient and reproducible, which optimizes its application in pathologic cases, especially those involving deformed orbits. Abstract : Supplemental Digital Content is available in the text